Behavioral finance: biased individual investment decision making; like the company but dislike the investment - Adrian MITROI (Theoretical and Applied Economics, 2014)

(untitled)
Classical economics considers people to be rational, self-interested and selfcontrolled. Behavioral economics showed instead that we are not as logical and efficient as we might think: we do care about others, and we are not as disciplined as we would like to be. Our intuitive mind works by mean of mental shortcuts that lead to erroneous decisions, since our mind delivers the products of these mental shortcuts, and we accept to follow them, spending the significant mental resources remaining available for other, survival related tasks.